Mortalidade neonatal associada à asfixia perinatal no estado de São Paulo : série histórica de 2004 a 2013 - Kawakami, Mandira Daripa [UNIFESP] (2017)
Objective:To analyze the temporal evolution of the neonatal deaths rate associated with perinatal asphyxia from 2004 to 2013 according to geographical distribution, gestational age (GA) and demographic variables in the State of São Paulo (SP State). Method: Populationbased study including deaths with perinatal asphyxia without congenital anomalies occurred during the first 27 days of life in São Paulo city, in the Metropolitan Area (Capital excluded) and in the countryside of the SP State from 2004 to 2013. Perinatal asphyxia was considered if intrauterine hypoxia, birth asphyxia or meconium aspiration syndrome were written in any line of the original Death Certificate (DC). Data was collected from SEADE Foundation after the linkage of the DC with its respective Birth Certificate based on the deterministic linkage process. The statistics analysis was assessed through Poisson regression model, Kaplan Meier curves, chi-squared test for trend and multivariate Cox regression. Results: From 2004 to 2013, 6,648 deaths resulted from perinatal asphyxia in SSP: 27% in São Paulo city; 21% in the Metropolitan Area (Capital excluded) and 52% in the countryside. The rates of neonatal death with asphyxia in 1,000 live births were 1.16 in 2004 to 0.97 in 2013 in São Paulo city (reduction of 17%; p=0.082); from 1.45 to 0.83 in the Metropolitan Area (reduction of 43%; p<0.001) and from 1.48 to 0.98 ( reduction of 34% ; p<0.001) in the country side. In neonates with 22 to 27 weeks, the reduction rate was higher in the Metropolitan Area than in São Paulo city (p=0.035) and also in neonates from 32 to 36 weeks in the Metropolitan Area (p=0.013) and in the countryside (p=0.003) compared to São Paulo city, with the same reduction rate among the 3 regions for 28-31 weeks and for 37-41 weeks. The median life time until death was 24 hours: higher in São Paulo city (36 hours), followed from the countryside (23 hours) and Metropolitan Area (21 hours). The extreme premature infants had the lowest median time of life (13 hours) and the highest was among the 28-31 weeks (41 hours). Births were more frequent in their hometown, with the reduction of births in SUS hospitals at the Metropolitan Area (p=0.034) and in the countryside (p=0.019), and deaths were more frequent at the same hospital of birth. Teenager mothers were less frequent (p=0.039), with higher rates of primiparous mothers (p<0.001) and cesarean deliveries (p=0.019) and with death reduction among 37-41 weeks (p<0.001) along the ten years. Based on multivariate analysis, adjusting the death year, there was an association of life time to death with: region and birth place, mother’s age, number of prenatal consultations, type of delivery, GA, 1st minute Apgar score, race/colour and sex. Conclusion: Neonatal deaths with perinatal asphyxia reduced significantly during 2004 to 2013, mainly among 32-36 weeks in the Metropolitan Area and in the countryside, most probably due to medical interventions and public policies directed to the pregnant mother and the newborns, which had a great impact in those regions in the State of São Paulo.